Endocrine regulation and metabolic mechanisms of osteopontin in the development and progression of osteosarcoma, metastasis and prognosis - Shao, Zhuce; Bi, Shuxiong (Frontiers in Endocrinology, 2023)
Abstract Osteosarcoma is the most common type of malignant bone tumour, occurring in adolescents and patients over 60 years of age, with a bimodal onset and a poor prognosis, and its development has not yet been fully explained. Osteopontin (OPN) is a high protein consisting of 314 amino acid residues with a negative charge and is involved in many biological activities. OPN is not only an important part of the regulation of the nervous system and endocrine metabolism of skeletal cells, but is also involved in a number of other important biological activities such as the division, transformation and proliferation of skeletal cells and their associated cells such as bone tumour cells, including bone marrow mesenchymal stem cells, haematopoietic stem cells, osteoblasts and osteoclasts. osteoblasts and osteocytes. Recent studies have shown a strong correlation between OPN and the development and progression of many skeletal diseases, such as osteosarcoma and rheumatoid arthritis.